Concise enantioselective syntheses of (+)-L-733,060 and (2S,3S)-3-hydroxypipecolicw acid by cobalt(III)(salen)-catalyzed two-stereocenter hydrolytic kinetic resolution of racemic azido epoxides - Devalankar, Dattatray A.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Synlett, 2014)
An efficient synthesis of the 2,3-disubstituted piperidines (+)-L-733,060 and (2S,3S)-3-hydroxypipecolic acid (99% ee) in high optical purity from commercially available starting materials is described. The strategy involves a cobalt-catalyzed hydrolytic kinetic resolution of a racemic azido epoxide with two stereocenters and an intramolecular reductive cyclization as key reactions.
Keywords: azides; cyclizations; epoxides; piperidines; stereoselective synthesis; Wittig reactions